Epigallocatechin‐Gallate: Unraveling Its Protective Mechanisms and Therapeutic Potential - Dong, Xiang‐Wen; Fang, Wen‐Lan; Li, Yun‐Hang; Chai, Yu‐Rong (Cell biochemistry and function, 2025)
ABSTRACT Epigallocatechin‐gallate (EGCG), the predominant catechin in green tea, is a key constituent of tea polyphenols. Due to the EGCG's diverse biological activities of anti‐inflammatory, antioxidant, and so forth, green tea is believed to exert a positive influence on a variety of diseases. And extensive research had uncovered a range of protective effects attributed to EGCG, indicating its potential to mitigate various pathological conditions. The precise mechanisms through which EGCG operates remain a subject of ongoing discussion among researchers. Reactive oxygen species (ROS), a primary culprit in oxidative stress, have been demonstrated to be reduced by EGCG. Furthermore, nuclear factor kappa‐B (NF‐κB), a pivotal signal molecular of inflammation progress, has been observed to be suppressed by EGCG. Sirtuins1 (Sirt1) is a histone deacetylase, the obligate substrate of which is NAD+. Evidence suggests that EGCG can enhance the activities of Sirt1 to induce autophagy to protect inflammation injury and oxidative stress in tissues and organs. Despite the promising protective effects of EGCG, its clinical use is constrained by its limited bioavailability. This review aims to consolidate the existing evidence and elucidate the mechanisms that support EGCG's protective role, as well as to explore the challenges and potential strategies for its clinical application. Summary This review aims to address the challenge of limited bioavailability of epigallocatechin‐gallate (EGCG). The originality of our approach lies in the comprehensive consolidation of existing evidence and the elucidation of mechanisms that support EGCG's protective role. We highlight the role of EGCG in reducing oxidative stress and inflammation through its action on ROS and NF‐κB, and its potential to induce autophagy via Sirt1 activation. We explore potential strategies to improve its clinical application and summarize recent clinical trials of EGCG in different conditions. This addresses the ongoing discussion among researchers regarding the precise mechanisms of EGCG and offers new insights into promoting its therapeutic effectiveness.